Planetary Period Oscillations in Saturn's Magnetosphere: Cassini Magnetic Field Observations Over the Northern Summer Solstice Interval. Issue 5 (31st May 2018) - Provan, G.; Cowley, S. W. H.; Bradley, T. J.; Bunce, E. J.; Hunt, G. J.; Dougherty, M. K.
Key Points: We measure properties of Saturn's planetary period oscillations using Cassini magnetic data over 2 years to end of mission in September 2017 Northern and southern system periods were near‐constant at 10.79 and 10.68 hr, respectively, almost unchanged since period reversal in 2014 Dual modulations were newly observed on polar field lines near the OCB with different character to equatorial modulations observed before